South-to-North gradient in lipid peroxidation in men with stable coronary artery disease in Europe - Grau, Maria; Guxens, Monica; Subirana, Isaac; Fito, Montserrat; Covas, Maria-Isabel; Jacquemin, Benedicte; Sunyer, Jordi; Lanki, Timo; Picciotto, Sally; Bellander, Tom; Katsouyanni, Klea; Schneider, Alexandra; et al. (European Heart Journal, 2007)
Aims: A South-to-North gradient across Europe exists for the incidence of coronary artery disease (CAD) rates. Low-density lipoprotein (LDL) oxidation is a hallmark of atherosclerosis and CAD development. The aim of our study was to determine whether differences exist in the degree of LDL oxidation in stable CAD patients from different regions of Europe. Methods and results: A cross-sectional multicentre study included 790 stable CAD male subjects aged 35–79 years (61.4 ± 9.5) from six European countries in three regions by latitude: Northern (Finland and Sweden), Central (Germany), and Southern (Greece, Spain, and Italy). Plasma oxidized LDL (oxLDL) levels were determined. Alcohol intake and lipid profile were significantly associated with oxLDL. The Italian participants had the highest oxLDL levels. A sensitivity analysis showed the models yielded higher adjusted oxLDL values in Northern (63.8 U/L) than in Central (57.6 U/L) and Southern populations (56.5 U/L), P < 0.001, after excluding Italian subjects. The probability of Southern Europe scoring the lowest oxLDL levels was >71% in all fitted models. Conclusion: Our findings suggest a gradient in LDL oxidation from Southern to Northern Europe that consistently holds for all levels of LDL, except for Italy; this country displays the highest levels in Europe, for unknown reasons.